(untitled) (Avocetta, 2018)
We present the fossil bird assemblage from the Middle Pleistocene deposits of Cava di Breccia di Casal Selce, which is one of the many fossil localities in the Ponte Galeria area (Roma, Italy). The fossil avian assemblage here described also represent one of the oldest Italian Pleistocene ones well described and highly differentiated. We detected the presence of 26 bird taxa which indicate that the environment of the Tiber paleodelta, during the Middle Pleistocene, was characterized mainly by extensive wetlands, open areas with scattered vegetation and woodlands. We documented the first occurrence of Egretta garzetta, Haematopus ostralegus and Turdus pilaris, and the first Italian occurrence of Aythya fuligula, Platalea leucorodia, Plegadis falcinellus, Accipiter nisus, and Haliaeetus albicilla.